2009
DOI: 10.1073/pnas.0909756106
|View full text |Cite
|
Sign up to set email alerts
|

Monkey drumming reveals common networks for perceiving vocal and nonvocal communication sounds

Abstract: Salient sounds such as those created by drumming can serve as means of nonvocal acoustic communication in addition to vocal sounds. Despite the ubiquity of drumming across human cultures, its origins and the brain regions specialized in processing such signals remain unexplored. Here, we report that an important animal model for vocal communication, the macaque monkey, also displays drumming behavior, and we exploit this finding to show that vocal and nonvocal communication sounds are represented by overlappin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 55 publications
(81 reference statements)
0
30
0
Order By: Relevance
“…Studies in nonhuman primates revealed an ability to integrate socially relevant multimodal cues from conspecifics (Ghazanfar and Logothetis, 2003), which is characterized by responsiveness of amygdala and auditory cortex (Ghazanfar et al, 2005;Remedios et al, 2009), superior temporal sulcus (STS) (Ghazanfar et al, 2008), and ventrolateral prefrontal cortex (Sugihara et al, 2006). However, it remained ambiguous whether this pattern was driven by emotional integration or low-level stimulus features.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in nonhuman primates revealed an ability to integrate socially relevant multimodal cues from conspecifics (Ghazanfar and Logothetis, 2003), which is characterized by responsiveness of amygdala and auditory cortex (Ghazanfar et al, 2005;Remedios et al, 2009), superior temporal sulcus (STS) (Ghazanfar et al, 2008), and ventrolateral prefrontal cortex (Sugihara et al, 2006). However, it remained ambiguous whether this pattern was driven by emotional integration or low-level stimulus features.…”
Section: Introductionmentioning
confidence: 99%
“…Macaque monkeys frequently produce such rhythmic gestures by shaking the branches of a tree or by hitting the ground, resulting in periodic sounds. Captive macaques exhibit a similar behavior by shaking environmental objects (53). Intriguingly, the rhythmic structure of this nonfacial acoustic gesture falls into the theta range as well, with typical frequencies around 5 Hz.…”
Section: Discussionmentioning
confidence: 83%
“…Using preferential-orienting tests, the behavioral relevance of such drumming sounds was demonstrated. Moreover, these acoustic gestures preferentially activate those auditory cortical regions known to be sensitive to vocal communication sounds (53), which may generate the prominent low-frequency rhythms observed in the auditory cortex (17). Thus, communicative audiovisual displays, whether produced using hands or orofacial structures, exhibit similar temporal organization, suggesting that the link between the rhythmic organization of cortical activity and the rhythmic structure of communication signals is general and effector-independent.…”
Section: Discussionmentioning
confidence: 99%
“…Tactile communication is intimate, involving skin-to-skin contact such as allogrooming and embracing (Weber 1973) and is used to maintain social structure, strengthen bonds between individuals, relieve stress and social agitation and maintain mother-infant attachments (Hertenstein et al 2006). Auditory communication can occur through vocalisations, as well as acoustic gestures such as tree buttress drumming (Arcadi et al 1998), branch shaking (Zhao 1997), chest-beating or hand-clapping (Kalan and Rainey 2009), and is used to express social status (Remedios et al 2009), defend territory, assist in agonistic confrontations and advertise alliances and group strength (Hagen and Hammerstein 2009). Finally, visual communication can involve the use of brachiomanual gestures such as arm-raising (Pollick and de Waal 2007) and beckoning (Hobaiter and Byrne 2011), facial expressions (Micheletta et al 2015) and body language/posture (Smith and Delgado 2015) to convey messages about an individual's internal state such as emotions and desires (Pika et al 2003;Parr et al 2005).…”
Section: The Differences Between Communication and Languagementioning
confidence: 99%